Exploring the potential of personalized VR bodily learning systems - Cain, Christine (2024)
Remote learning, also known as web-based learning or eLearning, provides opportunities for skill development and knowledge transfer without the need for teachers and learners to be co-located. This mode of education became essential during the Covid-19 pandemic lockdowns in 2020 and 2021. It is a model which largely relies on video conferencing software. But because of the desktop metaphor that has been foundational in the design of mainstream technology since the 1970s, these solutions are optimized for sharing information that is best recorded and interpreted on paper, i.e. flat, 2D interfaces. Meanwhile, individuals who wish to remotely access resources for bodily disciplines such as dance or martial arts currently must rely on these offerings as well. While it is not impossible to learn and teach bodily practices through these modalities, bodily knowledge ultimately lives in and is shared through the body, of which language and 2D visuals only provide an approximate translation. This thesis argues that there is ample opportunity in human computer interaction design to create new models of remote learning specifically for bodily practices, and makes use of virtual reality (VR) as one of the potential technological bases to ideate new fit-for-purpose models. As a maturing technology which still has not been widely adopted, VR allows some breathing room from the legacy language and symbolism that current remote learning models are built upon. And most importantly, it affords more physical interactions, making it a suitable candidate for body-first design explorations.